IMPLEMENTASI MODEL PEMBELAJARAN TEACHING AT THE RIGHT LEVEL UPAYA UNTUK MEMPERBAIKI KECAKAPAN LITERASI MEMBACA SISWA DI UPT SD NEGERI BATURETNO 1 TUBAN - Lestari, Ayu Nanda; Wendri Wirastiwi (Jurnal Tunas Pendidikan, 2025)
The TaRL approach is a really effective way to improve the basic reading skills of young elementary students. By using this model, educators have three main goals: (1) to adjust teaching methods to fit each student’s abilities, (2) to create a more engaging and confident learning environment, and (3) to assess how students are doing in order to inform future lessons.The community service project takes a comprehensive approach that includes (1) observing students, (2) giving lectures, and (3) providing hands-on training. When the TaRL model was put into practice, there were noticeable improvements in students’ reading skills. After participating in this tailored learning program, students showed significant progress, which supports the idea of using this approach more widely in elementary schools.